Effect of Financial Performance and Firm Size on Stock Price with Dividend Policy as Intervening Variable - Novita Andriani; Achmad Hizazi; Rita Friyani (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the effect of profitability, liquidity, solvency, and firm size on stock prices with dividend policy as an intervening variable in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research employed a quantitative approach with a causal associative method. The data used were secondary data obtained from audited annual financial reports. The sample was determined using purposive sampling, resulting in 70 companies that met the research criteria. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach and SmartPLS 4 software. The results show that profitability, solvency, and firm size have a significant direct effect on stock prices, while liquidity and dividend policy do not have a significant effect. Moreover, dividend policy does not mediate the relationship between profitability, liquidity, solvency, and firm size on stock prices. These findings suggest that dividend decisions are not yet strong enough to serve as market signals influencing stock price movements in the food and beverage sector. Nevertheless, the results confirm that the company's fundamental factors still contribute significantly to investor decision-making, especially through profitability and firm size indicators. This study is expected to provide valuable insights for investors, corporate management, policymakers, and academic literature development in the fields of financial management and capital markets